2013
DOI: 10.1128/aac.01364-13
|View full text |Cite
|
Sign up to set email alerts
|

Cell Culture-Selected Substitutions in Influenza A(H3N2) Neuraminidase Affect Drug Susceptibility Assessment

Abstract: Assessment of drug susceptibility has become an integral part of influenza virus surveillance. In this study, we describe the drug resistance profile of influenza A(H3N2) virus, A/Mississippi/05/2011, collected from a patient treated with oseltamivir and detected via surveillance. An MDCK cell-grown isolate of this virus exhibited highly reduced inhibition by the neuraminidase (NA) inhibitors (NAIs) oseltamivir (8,005-fold), zanamivir (813-fold), peramivir (116-fold), and laninamivir (257-fold) in the NA inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 29 publications
5
43
0
2
Order By: Relevance
“…The effect of S247P on the enzymatic activity on the recNA was next investigated as previously described (32). When expressed either alone or together with S245N, S247P reduced by 60% the recNA's ability to cleave a small synthetic substrate MUNANA, compared to the wild-type recNA (data not shown).…”
Section: Susceptibilities Tomentioning
confidence: 86%
“…The effect of S247P on the enzymatic activity on the recNA was next investigated as previously described (32). When expressed either alone or together with S245N, S247P reduced by 60% the recNA's ability to cleave a small synthetic substrate MUNANA, compared to the wild-type recNA (data not shown).…”
Section: Susceptibilities Tomentioning
confidence: 86%
“…The present study also showed no significant variations in IC 50 s arising from virus propagation. Nevertheless, participating laboratories were advised by the CDC to limit the number of virus passages since it could lead to emergence of NA changes resulting in elevated IC 50 s (Tamura et al, 2013;Mishin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed using the NA-Fluor™ Influenza Neuraminidase Assay Kit (Applied Biosystems/Life Technologies, Carlsbad, CA) in 96-well opaque black flat-bottom microplates (Corning Inc., Corning, NY), according to the CDC protocol, which can be requested by email (fluantiviral@cdc.gov). The CDC fluorescent NI assay protocol is optimized to the needs of virological surveillance (OkomoAdhiambo et al, 2013) and somewhat differs from the manufacturer's instructions in the NA-Fluor™ kit manual. Briefly, viruses were diluted at concentrations corresponding to the target fluorescence signal generated by 1000 pmol/well of 4-methylumbelliferone (4-MU) standard.…”
Section: Neuraminidase Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Culturing A/H3N2 influenza viruses has been shown to alter the influenza antiviral drug susceptibility profile as assessed in NA inhibition assays. When the NA of cultured virus is subsequently sequenced, reduced or additional variant populations may be observed (25,26). This highlights one of the difficulties in assessing the influenza antiviral susceptibility profiles of patients undergoing antiviral treatment and emphasizes the importance of the direct analysis of specimens with multiple testing methods (27).…”
Section: Na-fluor Phenotypic Testingmentioning
confidence: 99%